2006
DOI: 10.2337/dc06-0243
|View full text |Cite
|
Sign up to set email alerts
|

Brain Aging in Very Old Men With Type 2 Diabetes

Abstract: OBJECTIVE -Type 2 diabetes leads to cognitive impairment and dementia, which may reflect microvascular and macrovascular complications as well as neurodegenerative processes. There are few studies on the anatomical basis for loss of cognitive function in type 2 diabetes. The objective of this study was to investigate the association between type 2 diabetes and markers of brain aging on magnetic resonance images, including infarcts, lacunes, and white matter hyperintensities as markers of vascular damage and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(120 citation statements)
references
References 46 publications
12
106
0
2
Order By: Relevance
“…Investigators studying cases from a large epidemiological sample have shown that, relative to nondiabetic control subjects, elderly (average age 77.8 years) individuals with type 2 diabetes exhibit reductions in hippocampal and amygdalar volumes [7]; however, no neuropsychological data were reported in this sample. A moderately elevated risk of hippocampal atrophy (odds ratio 1.7, 95% CI 0.9-2.9) has been demonstrated among very old men with type 2 diabetes [8], but it should be noted that this study included individuals with dementia, Alzheimer's disease, strokes, lacunes and high rates of white matter disease.…”
Section: Introductionmentioning
confidence: 83%
“…Investigators studying cases from a large epidemiological sample have shown that, relative to nondiabetic control subjects, elderly (average age 77.8 years) individuals with type 2 diabetes exhibit reductions in hippocampal and amygdalar volumes [7]; however, no neuropsychological data were reported in this sample. A moderately elevated risk of hippocampal atrophy (odds ratio 1.7, 95% CI 0.9-2.9) has been demonstrated among very old men with type 2 diabetes [8], but it should be noted that this study included individuals with dementia, Alzheimer's disease, strokes, lacunes and high rates of white matter disease.…”
Section: Introductionmentioning
confidence: 83%
“…The glucose-mediated effects on cognition and brain structure might accelerate brain ageing. In addition, neurotoxic AGE caused by hyperglycaemia may contribute to the formation of neurofibrillary tangles and neuritic plaques [47]. Second, insulin resistance, especially in earlystage diabetes, is associated with compensatory hyperinsuli-naemia.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin appears to stimulate beta-amyloid peptide secretion and inhibit the extracellular degradation of beta-amyloid by competition for insulin-degrading enzyme (IDE) [48]. Insulin signalling defects may increase hyperphosphorylation of tau protein, which can lead to neurofibrillary tangles [47]. Third, inflammatory markers, including C-reactive protein, IL-6 and TNF-α1 are associated with diabetes and also contribute to the development of Alzheimer's disease [49].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes also is associated with cognitive disorders (13-15) and with brain structural changes in large and small vessels (16,17). Therefore, it is biologically plausible to hypothesize that the strength of association between retinal and cerebral microvascular lesions may be greater in people with diabetes compared with those without the disease.…”
Section: Results-evidencementioning
confidence: 99%